2007
DOI: 10.1007/s10762-007-9305-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Effect of Dielectric Loss on RF Characteristics of Helical SWS

Abstract: A general theory has been developed to account for the effect of the dielectric loss of discrete rods on the performance characteristics of an actual helical slow wave structure (SWS). The effect of the lossy dielectric rods has been studied on various propagation parameters, namely, phase propagation constant, interaction impedance and attenuation constant at different operating frequency. It is clearly shown that the influence of dielectric loss on RF characteristics is much larger at the millimeter frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…2 vis-à-vis published theoretical results of Duan, et al [11]. The present simple method shows excellent agreement against that of a rigorous and computation intensive tape-helix model.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…2 vis-à-vis published theoretical results of Duan, et al [11]. The present simple method shows excellent agreement against that of a rigorous and computation intensive tape-helix model.…”
Section: Discussionsupporting
confidence: 71%
“…The method consists in finding the shunt capacitance (C) and shunt conductance (G) per unit length of the transmission line equivalent to the SWS, and then interpreting these parameters for the dielectric attenuation constant of the structure. The formula thus arrived at has been benchmarked against published results of Duan, et al [11] and excellent agreement was found. The analysis has been subsequently applied in predicting the dielectric loss in typical C-Ku band and Ka band helical SWSs, and variation of dielectric loss with temperature.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations